2013
DOI: 10.1074/jbc.m113.489278
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine/Paracrine Function of Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) for Glucose Homeostasis in Pancreatic β-Cells and Adipocytes

Abstract: Background: External application of a Ca 2ϩ -mobilizing messenger, NAADP, to ␤-cells activates intracellular Ca 2ϩ changes and stimulates insulin secretion. Results: NAADP is transported into adipocytes and ␤-cells in a glucose-dependent manner and is also released from pancreatic islets upon stimulation by high glucose. Conclusion: NAADP functions in an auto-/paracrine manner to regulate glucose homeostasis. Significance: NAADP can be exploited as a potential antidiabetic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…In line with our previous report that NAADP has paracrine functions in glucose homeostasis (37), it would be interesting to know whether exercise brings additional benefits for glucose homeostasis, specifically if the increased NAADP levels in skeletal muscle during exercise could be released into the blood stream through cell damage or another unidentified mechanism, NAADP would act on pancreas b-cells and adipocytes for insulin secretion and glucose uptake, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…In line with our previous report that NAADP has paracrine functions in glucose homeostasis (37), it would be interesting to know whether exercise brings additional benefits for glucose homeostasis, specifically if the increased NAADP levels in skeletal muscle during exercise could be released into the blood stream through cell damage or another unidentified mechanism, NAADP would act on pancreas b-cells and adipocytes for insulin secretion and glucose uptake, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Inactivation or inhibition of NAADP receptors blunted the glucose-induced [Ca 2+ ] c rise [123] [221,224]. NAADP has recently been suggested to act as an autocrine or paracrine signal for ␤-cell since its extracellular application at submicromolar concentrations increased [Ca 2+ ] c possibly as a result of its uptake by the cell [225]. A release of Ca 2+ from endo/lysosomes independent of NAADP and involving RyR has also been suggested in ␤-cells [132].…”
Section: Acidic Ca 2+ Storesmentioning
confidence: 99%
“…2 (23) and in a rat basophilic cell line (24). Recent reports further showed that exogenous NAADP was transported into human lymphokine-activated killer cells and induced Ca 2ϩ release from lysosomal-like acidic stores in those cells (25) and in mouse pancreatic ␤ cells and adipocytes (26). These observations prompted us to test this approach to investigate the NAADP-mediated Ca 2ϩ release mechanism in a more specific manner through direct activation of Ca 2ϩ release in naive T cells by NAADP.…”
Section: Naadpmentioning
confidence: 99%
“…We examined uptake of external NAADP into the cells by a [ 32 P]NAADP transport experiment similar to that used to demonstrate uptake by pancreatic ␤ cells (26) and LAK cells (25). CD4 T cells showed a concentration and time-dependent increase in [ 32 P]NAADP (Fig.…”
Section: Naadpmentioning
confidence: 99%
See 1 more Smart Citation